Persepsi masyarakat Suku Amungme dan Suku Kamoro terhadap manfaat program pengembangan ekonomi PT. Freeport Indonesia di Kabupaten Mimika (2008-2009) - AKAS, Yunita ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This study aims to analyze Amungme and Kamore tribe public perception against the benefits of fund program of PT Freeport Indonesia, which is channeled through LPMAK, comparing the perceptions between the Amungme and Kamoro public. The data used are primary data obtained from respondents answers to questionnaires and interviews and secondary data derived from LPMAK. The analytical method used is the analysis of the Likert Scale and the Mann-Whitney Test. The results show that the implementation of the assistance program has been established to Amungme and Kamoro tribes about the benefits of the program. The perception created in the community is that the program is beneficial. There are three ranks highest benefit is: the creation of business opportunities, the capital support, and creation of jobs. Based on the different test results, with a value of z is -2.928 and the asymptotic significance (two-tailed) is 0.003, the results indicate that there are significant differences in perception among the beneficiaries of the revolving fund program Amungme and Kamoro tribes.